KONSUMSI RUMAHTANGGA PETANI DI WILAYAH TAMAN NASIONAL LORE LINDU (TNLL) (SUATU KASUS DI DESA KATU KECAMATAN LORE TENGAH KABUPATEN POSO PROPINSI SULAWESI TENGAH) - Arifuddin Lamusa (Universitas Tadulako, 2007)
The objectives of the research of farmer household consumption in the margin area of the Lore Lindu National Park were: 1) to study the factors influencing the food consumption pattern of the farmer household at the Katu Village, 2) to determine the model of consumption function of the farmer household, 3) to determine the total income of the farmer household, 4) to study the portion of on farm and off farm/non farm income from total income of farmer household, 5) to study the expenditure of farmer household of food and non food consumption at the Katu Village. The results showed that: The factors which have influenced to the food consumption pattern of farmer household at the Katu Village are: a) income (X1), b) the number of the farmer household members (X2), c) age (X3), d) education (X4), and respondent status in the village. The sum of variables has significant influenced to the dependent variable (Y) namely: X1, X2, and X4. The model of consumption function of the farmer household is: Y = 0.13504 + 0.49997X1 + 0.29622X2 + 0.16344X3 + 0.3324X4 + 0.14283D. The consumption pattern of farmer household at the Katu Village is: Cassava-rice/rice-corn with such side dish as fish, met, eggs, vegetables, and fruits. The consumption expenditure of farmer household is IDR 4.383,63/year equal to IDR 365,280.55/month. The total expenditure for food is 54.2 % and for non food 45.8 %. The total income generated from two sources is IDR 491,583.36/month equal to IDR 5,899 million/year.